A cluster analysis of road traffic-related childhood knee injuries. - Iakovakis, I; Dessypris, N; Dalamaga, M; Petridou, E (Child Care Health Dev, 2003)
BACKGROUND: Knee injuries represent an important category of road traffic injuries among children, and they are heterogeneous in their aetiology. The aims of this study were to estimate the incidence of road traffic childhood knee injuries in Greece by age and gender, point out their time, place and person co-ordinates and identify clusters with distinct characteristics with a view to potential preventive interventions. METHODS: During a 3-year period, 305 children with knee injuries resulting from a road traffic accident were identified among the 66,870 children with injuries recorded in the Emergency Department Injury Surveillance System (EDISS) of Greece. Using previously derived sampling ratios and national data on childhood population, incidence data by age and gender were estimated. Hierarchical analysis was undertaken for cluster identification. RESULTS: The incidence of road traffic knee injuries was 97.5 per 100,000 children-years. The incidence increased with age and was higher among boys than among girls. Most childhood knee injuries (50.2%) occur among pedestrians, and the majority (90.9%) of the children or their guardians admitted responsibility in crossing the road. Of the 31 children injured as car passengers, the vast majority (87.1%) were unrestrained, and a large fraction (38.7%) were front seat passengers. Two clusters were identified: the first consisted of younger children who resided mostly in the Athens area and suffered less serious knee injuries as pedestrians or car passengers during the colder months; the second consisted of older children, frequently tourists, who suffered more serious injuries as cyclists while vacationing. CONCLUSIONS: Many of the children who suffered road traffic knee injuries as pedestrians admitted responsibility in road crossing, whereas a large proportion of children who were injured as car passengers were injured while improperly seated in the front and without seatbelt protection. Older children, frequently tourists, were at high risk of knee injuries while using motorcycles and bicycles.
Keywords: Accidents, Traffic; Adolescent; Child; Child, Preschool; Cluster analysis; Female; Greece; Humans; Infant; Infant, Newborn; Knee Injuries; Male; Risk Factors